Chitosan-Coated Liposome Formulations for Encapsulation of Ciprofloxacin and Etoposide - Rubén Gil-Gonzalo; D. Alonzo Durante-Salmerón; Saeedeh Pouri; Ernesto Doncel-Pérez; Andrés R. Alcántara; Inmaculada Aranaz; Niuris Acosta (MDPI AG, 2024)
Cancer and bacterial infections rank among the most significant global health threats. accounting for roughly 25 million fatalities each year. This statistic underscores the urgent necessity for developing novel drugs, enhancing current treatments, and implementing systems that boost their bioavailability to achieve superior therapeutic outcomes. Liposomes have been recognised as effective carriers; nonetheless, they encounter issues with long-term stability and structural integrity, which limit their pharmaceutical applicability. Chitosomes (chitosan-coated liposomes) are generally a good alternative to solve these issues. This research aims to demonstrate the effective individual encapsulation of ciprofloxacin (antibacterial, hydrophilic) and etoposide (anticancer, hydrophobic), within chitosomes to create more effective drug delivery systems (oral administration for ciprofloxacin, parenteral administration for etoposide). Thus, liposomes and chitosomes were prepared using the thin-film hydration technique and were characterised through ATR-FTIR, Dynamic Light Scattering (DLS), zeta potential, and release profiling. In both cases, the application of chitosomes enhanced long-term stability in size and surface charge. Chitosome-encapsulated ciprofloxacin formulations exhibited a slower and sustained release profile, while the combined effect of etoposide and chitosan showed heightened efficacy against the glioblastoma cell line U373. Therefore, coating liposomes with chitosan improved the encapsulation system's properties, resulting in a promising method for drug delivery.